Secret at Pebble Creek - Baker, Lisa Jones (Baker, Lisa Jones. Hope chest of dreams., 2018)
When Jessica Beachy temporarily moves into the home of her late great uncle, Sam Beachy, she merely plans to remodel, sell, and head back to the city. She<U+2019>s used to busy St. Louis and can<U+2019>t imagine how she<U+2019>ll spend her time in the quiet Amish countryside. But the carpenter she hires, Eli Miller, doesn<U+2019>t think selling Sam<U+2019>s home is a good idea. And while he<U+2019>s steadfast in his Amish faith, he<U+2019>s instantly drawn to Jessica<U+2019>s vivacity and unexpected caring<U+2014>especially as peaceful country ways make her question the dream she thought she wanted . . . But a lucrative offer to turn the house into a vacation retreat confronts Jessica with a heartbreaking choice. It will take trust, perseverance<U+2014>and discovering a hope chest thought forever lost<U+2014>for Jessica and Eli to boldly face obstacles and embark on a joyous future together . . .